1990
DOI: 10.1007/bf01907111
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of acute normovolemic hemodilution in rats with disopyramide-induced myocardial depression

Abstract: The effect of myocardial depression on the circulatory response to acute normovolemic hemodilution (hematocrit 23%) with hetastarch was evaluated in 28 anesthetized Sprague-Dawley rats. Cardiac output was recorded using an electromagnetic flow probe. Mild, moderate, and severe myocardial depression were achieved by infusing disopyramide 50, 75, and 85 mg/kg. This resulted in a dose-dependent decrease in cardiac output (r = -0.73, p less than 0.05) and mean arterial pressure (r = -0.65, p less than 0.05), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 39 publications
(33 reference statements)
2
4
0
1
Order By: Relevance
“…These results are in agreement with the work reported by Estafanous et al and Shinoda et al in their control group, but differ from that Murray et al , who found that hemodilution slightly increases MAP and HR [10, 23, 29]. The marked decrease in SVR and SVH after HVPE hemodilution implies geometrical change in the vasculature to explain the reduced resistance, compared to LVPE.…”
Section: Discussionsupporting
confidence: 89%
“…These results are in agreement with the work reported by Estafanous et al and Shinoda et al in their control group, but differ from that Murray et al , who found that hemodilution slightly increases MAP and HR [10, 23, 29]. The marked decrease in SVR and SVH after HVPE hemodilution implies geometrical change in the vasculature to explain the reduced resistance, compared to LVPE.…”
Section: Discussionsupporting
confidence: 89%
“…The individual flow compared with filling pressure curves reflected the large variability in haemodynamic response to ANH, regardless of preoperative left ventricular ejection fraction. Likewise, previous studies performed in patients with CAD and in animals with a myocardial infarct or disopyramide‐induced myocardial insufficiency, have indicated that the increase in cardiac output during ANH was largely independent of ventricular function [33, 34].…”
Section: Discussionmentioning
confidence: 89%
“…43 Acute administration of negative inotropic agents like anti-arrhythmic drugs or β-blocking agents will also reduce the cardiac output response to ANH. 25,44 In the postoperative period, tolerance of patients with altered myocardial function will closely depend on the potential recovery of their cardiac function and, again, on the level of metabolic demand.…”
Section: Anh and Altered Cardiac Functionmentioning
confidence: 99%